Biosynthesis During Recovery of Heat-Injured Salmonella typhimurium - Pierson, Merle D. (1971)
Salmonella typhimurium 7136 incorporated label from glucose-U-(14)C into nucleic acids, lipids, and pool material during recovery from heat injury. There was very little incorporation of label into protein during recovery.